A Comparison of Legislative Election Systems in Indonesia and Malaysia - Nugroho, Rahmat Muhajir; Asmorojati, Anom Wahyu; Setyaningrum, Wita; Shuaib, Farid Sufian (Jurnal Media Hukum, 2000)
The article aimed to analyze the comparison of electoral systems in Indonesia and Malaysia due to relevant differences and similarities. In Malaysia, the legislative election system was implemented to elect members of the People Council using a district platform. Meanwhile, Indonesia used an Open Proportional system to elect members of the National and Regional Representative Councils. A total of three aspects were also compared between both countries through a legal research and comparative approach, namely Government, Election, and Party Systems. Data collection was subsequently carried out through empirical studies, including interviews and literature reviews. The results showed that differences in government systems, state forms, and administration were observed between Indonesia and Malaysia, where proportional and district electoral platforms were implemented, respectively. Despite the differences, the two countries still had various similarities, such as the implementation of a multiparty system using different party coalition platforms. Variations were also observed in the implementation of voting rights by soldiers and convicts within both countries.